Approaching a high-rate and sustainable production of hydrogen peroxide: oxygen reduction on Co–N–C single-atom electrocatalysts in simulated seawater. Issue 10 (31st August 2021) - Zhao, Qinglan; Wang, Yian; Lai, Wei-Hong; Xiao, Fei; Lyu, Yuxiang; Liao, Caizhi; Shao, Minhua
Abstract : Sustainable production of H2 O2 is boosted by oxygen reduction reaction on Co–N5 sites in a flow cell in simulated seawater. Abstract : Electrochemical production of H2 O2 from O2 using simulated seawater provides a promising alternative to the energy-intensive industrial anthraquinone process. In this study, a flow cell system is built for electrocatalytic production of H2 O2 under an air atmosphere in simulated seawater using cobalt single-atom catalysts (Co SACs). The Co SACs can achieve a high H2 O2 production rate of 3.4 mol gcatalyst −1 h −1 under an air flow at a current density of 50 mA cmgeo −2 and long-term stability over 24 h in 0.5 M NaCl. It is found that Co–N5 rather than the Co–N4 structure in Co SACs is the main active site for H2 O2 formation in the two-electron oxygen reduction reaction (ORR) pathway. It also shows high chloride-endurability without inhibition of the ORR process in simulated seawater. The fast production of H2 O2 on Co–N5 sites in a flow cell provides a promising path of electrocatalytic oxygen reduction in simulated seawater, eventually converting ubiquitous air and seawater towards energy sustainability.